PROPOSTA DE CRITÉRIOS PARA ELABORAÇÃO DE UM PROGRAMA DE QUALIDADE DE VIDA NO TRABALHO COM BASE NO SERVIÇO DE SAÚDE OCUPACIONAL (SESAO) - INMETRO - Ballerini, Sérgio (2007)
This work describes a methodology for total quality administration, looking to comply Portaria 32/2002 of the National Institute of Metrology, Standardisation and Industrial Quality - INMETRO. INMETRO is a federal autarchy linked to the Ministry of the Development, Industry and External Commerce, which acts in the areas of Scientific and Legal Metrology, Quality, Certification and Standardisation. The improvement of workers performance, was the central focus it was achieved by investing in programs of life quality, seeking to improve the physical and psychic conditions of the institute Workforce, reducing the possibility of diseases in search of physical and mental health balance. The results show an increasing on workforce productivity, prevention of diseases, social integration and a decrease in the absenteeism. The local community's participation is emphasised in several projects complying with the goals of the institution mission: "The promotion of citizen's life quality, and the competitiveness of the economy through the metrology and industrial quality . After the implementation of this program and during the last two years, it was registered a very small absenteeism, a reduction around 50% of benefits concession regarding insalubrity/danger, reduction of 17% in the number of the indenfied chemical dependent and a general increase in the personal motivation of INMETRO workforce. Thesa wre the basic directions of the is a program which has of Social Responsibility as one of its adjectives